2017
DOI: 10.1002/2017gl074611
|View full text |Cite
|
Sign up to set email alerts
|

Classifying the tropospheric precursor patterns of sudden stratospheric warmings

Abstract: Classifying the tropospheric precursor patterns of sudden stratospheric warmings (SSWs) may provide insight into the different physical mechanisms of SSWs. Based on 37 major SSWs during the 1958–2014 winters in the ERA reanalysis data sets, the self‐organizing maps method is used to classify the tropospheric precursor patterns of SSWs. The cluster analysis indicates that one of the precursor patterns appears as a mixed pattern consisting of the negative‐signed Western Hemisphere circulation pattern and the pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…In contrast, the S2S models simulated more frequent polar stratospheric easterlies during EN over this period ( Figure 5). This discrepancy between the models and observations as to which ENSO phase preferentially leads to more SSW is consistent with the discrepancy in the ridging over eastern Europe (Bao et al, 2017;Cohen & Jones, 2011;Kretschmer et al, 2017).…”
Section: Discussion and Summarysupporting
confidence: 76%
See 1 more Smart Citation
“…In contrast, the S2S models simulated more frequent polar stratospheric easterlies during EN over this period ( Figure 5). This discrepancy between the models and observations as to which ENSO phase preferentially leads to more SSW is consistent with the discrepancy in the ridging over eastern Europe (Bao et al, 2017;Cohen & Jones, 2011;Kretschmer et al, 2017).…”
Section: Discussion and Summarysupporting
confidence: 76%
“…The stratospheric response to EN events is driven by a deepened Aleutian low (e.g., Barnston & Livezey, ), which constructively interferes with the climatological stationary planetary wave pattern and leads to strengthened wave flux into the stratosphere (i.e., linear interference; Garfinkel & Hartmann, ; Garfinkel et al, ; Smith et al, ; Smith & Kushner, ), as recently reviewed by Domeisen et al (). Other modes of tropospheric variability (e.g., October Eurasian snow) can affect the vortex through a similar pathway but via variability over western Siberia/eastern Europe, where a ridge constructively interferes with the climatological stationary planetary wave pattern and leads to strengthened wave flux into the stratosphere (Bao et al, ; Cohen & Jones, ; Garfinkel et al, ; Kretschmer et al, ). Episodes of prolonged upward wave flux can lead to sudden stratospheric warming (SSW) events (Polvani & Waugh, ; Sjoberg & Birner, ), induce a tendency toward a negative phase of the North Atlantic Oscillation (Bell et al, ; Ineson & Scaife, ), and increase weather predictability (Sigmond et al, ) in the Euro‐Atlantic region for more than a month.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Bao et al . () demonstrated lows over the Western Hemisphere, and highs over Pacific–North America to be an even stronger precursor to SSWs than Pacific lows and European highs.…”
Section: Introductionmentioning
confidence: 87%
“…Surface pressure lows and decreased blocking in the northern Pacific, along with surface highs and increased blocking in Europe are connected to vortex disturbances by constructive interference with climatological planetary waves (Garfinkel et al, 2010;Huang et al, 2017). Furthermore, Bao et al (2017) demonstrated lows over the Western Hemisphere, and highs over Pacific-North America to be an even stronger precursor to SSWs than Pacific lows and European highs.…”
Section: Introductionmentioning
confidence: 99%
“…Tropospheric blocking is one such feature (e.g., Colucci & Kelleher, ; Garfinkel et al, ; Julian & Labitzke, ; Martius et al, ; Quiroz, ). For example, Bao et al () used cluster analysis to assess 500‐hPa geopotential height patterns in the month before 37 SSWs in reanalysis and found the patterns to be associated with linear interference with climatological stationary waves. Kolstad and Charlton‐Perez () used reanalysis alongside climate model simulations and found a particularly strong signal for a height anomaly dipole over northern Eurasia preceding “weak vortex months.” Other studies have considered more transient features associated with specific stratospheric events.…”
Section: Introductionmentioning
confidence: 99%